The Role of Traceability in Food Recall Management: A Systematic Literature Review - Pulita, João Guilherme; Canesin, Helena; Oliveira, Lucas Lima de; Silva, Andrea Lago da; Pereira, Carla Roberta (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose - A gap has been observed regarding the use of traceability in the context of risk management in food supply chains. Recent studies on product recalls mostly focus on durable goods, while research aimed at risk management in food recalls is scarce. The aim of this study is to understand how traceability influences food recall management. Theoretical framework - Initially, the fundamental concepts of food traceability, its objective and impacts on supply chains were defined. Then, its relationship with food recalls was described. Design/methodology/approach - A systematic literature review (SLR) was conducted. A total of 75 selected articles were submitted to content analysis using QDA Miner software. Findings - Ten main applications of traceability in food chains (emphasizing the role of transparency) and three groups of risks were identified that lead to the occurrence of food recalls (operational, biological, and chemical). Finally, the role of traceability before (preparation stage - proactive nature), during (response stage), and after (recovery stage) the occurrence of a food recall was determined. Research, practical & social implications - The results provide a better understanding of the role of traceability in food recall management. Originality/value - The article summarizes ten different applications of traceability in the food chain, in addition to explaining the role of traceability in the different stages of food recall management. Keywords - Traceability. Recall. Supply Chain. Food.